Simplification to dual therapy containing lamivudine and raltegravir or dolutegravir in HIV-infected patients on virologically suppressive antiretroviral therapy. (30th July 2020) - Calza, Leonardo; Colangeli, Vincenzo; Borderi, Marco; Testi, Diletta; Granozzi, Bianca; Bon, Isabella; Re, Maria Carla; Viale, Pierluigi
Abstract: Background: Antiretroviral dual regimens including lamivudine and one boosted PI or dolutegravir are warranted in order to optimize combination ART (cART), prevent long-term toxicity and reduce the cost of treatments. Objectives: We hypothesized that a maintenance dual regimen of lamivudine plus raltegravir would be effective and as well tolerated as the dual maintenance combination of lamivudine plus dolutegravir. Methods: We performed an observational, retrospective study of HIV-infected patients on suppressive ART who switched to a dual regimen containing lamivudine 300 mg once daily plus raltegravir 1200 mg once daily or dolutegravir 50 mg once daily. Results: In total, 109 patients (79 men; mean age 46.4 years; mean CD4+ T lymphocyte count 605 cells/mm 3 ) were enrolled. Overall, 50 subjects switched to lamivudine plus raltegravir (Group A) and 59 to lamivudine plus dolutegravir (Group B). After 12 months, 45 patients (90%) in Group A and 52 (88.1%) in Group B had HIV RNA <20 copies/mL. No patients had severe adverse effects in either group, and the percentages of patients with mild adverse effects were comparable, except for a higher incidence of headache and sleeping disturbances in Group B than in Group A (30.5% versus 14%, P < 0.001). A comparable and non-significant weight increase was reported in both groups (+1.91 kg in Group A and +2.28 kg in Group B). Conclusions: In our study, dual therapies containing lamivudine plus raltegravir or dolutegravir in virologically suppressed patients showed high and comparable efficacy, as well as good tolerability.